Urgensi Pembelajaran Pendidikan Agama Islam Multikultural - Assayuthi, Jalaludin (Atthulab: Islamic Religion Teaching and Learning Journal, 2020)
Islamic education is an education that gives the knowledge for studentâ€™s attitude, skills, and personalities to apply Islamic doctrine. While, multicultural education is an educational strategy which is applied in teaching curriculum with the important point is emphasis in diversity. Which means, the difference social background, economic, religion, language, ethnic, gender, and student ability. This research wants to explain that multicultural education is an important education to be implemented in SMK Medina, Bandung. This research uses qualitative research with multicultural education approach by Lawrence A. Blum. (1). Knowledge is clarifying individual cultural identity, studying and evaluating individual culture inheritance. (2). Attitude is respecting and learning about cultures beside their own culture. (3). Instructional is looking other different culture as a positive kindness to appreciate and protect. Blum multicultural education approach is a concept which compare to Islamic education as educational strategy can be applied on teaching curriculum in high school or it is equivalent. The result of this research is multicultural education in SMK Medina, Bandung become important, because as a tools for student to build moderate and tolerant. With this attitude, student can appreciate and respect other student background. So that, from that attitude can be a way for student to solve the conflict among student. Â Abstrak Pendidikan Agama Islam (PAI) merupakan pendidikan yang memberikan pengetahuan untuk membentuk sikap, kepribadian dan keterampilan siswa dalam mengamalkan ajaran Islam. sementara itu, pendidikan multikultural merupakan strategi pendidikan yang diaplikasikan dalam kurikulum pengajaran dengan poin penting yang menekankan pada keragaman. Keragaman yang dimaksud adalah perbedaan latar belakang sosial, ekonomi, agama, bahasa, etnis, gender dan kemampuan siswa. Penelitian ini hendak menjelaskan bahwa pendidikan multikultural merupakan pendidikan yang penting untuk diimpelementasikan di SMK Medina Kota Bandung. Metode yang digunakan adalah kualitatif dengan menggunakan pendekatan pendidikan multikultural dari Lawrence A. Blum. (1) Knowledge, yaitu menegaskan identitas kultural seseorang, mempelajari dan menilai warisan budaya seseorang. (2) Attitude, yaitu menghormati dan belajar tentang kebudayaan-kebudayaan selain kebudayaannya. (3) Instructional, yaitu memandang budaya lain yang berbeda sebagai kebaikan yang positif untuk dihargai dan dipelihara. Pendekatan pendidikan multikultural Blum adalah sebuah konsep yang dikomparasikan dengan PAI sebagai strategi pendidikan yang dapat diaplikasikan dalam kurikulum pengajaran di sekolah menengah atas atau sederajat. Hasil penelitiannya adalah pembelajaran pendidikan multikultural di SMK Medina Kota Bandung menjadi penting, karena sebagai sarana bagi siswa agar dapat menanamkan sikap moderat dan toleran. Dengan sikap moderat dan toleran, siswa dapat saling menghargai dan menghormati latar belakang siswa lainnya yang beragam. Sehingga, dengan kedua sikap ini juga dapat menjadi sarana bagi siswa untuk menyelesaikan konflik yang terjadi di antara siswa.